Impact of physical-health-improving activities in out-school sections on the health level of pupils of 5–6 classes - Hatsko, Elena; Yevdokymova, Lilia; Solianyk, Tatyana; Pushkarov, Yuri (ScienceRise: Pedagogical Education, 2017)
The aim of research is to determine the influence of sectional training in health-improving running on the health level of pupils of the middle school age. 28 pupils of 5–6 classes took part in the research. The duration of pedagogical experiment was 8 months. The activities took place 5 times a week: physical training 3 times, according to the learning program for secondary educational institutions, and pupils visited the section of health-improving walking and running 2 times, during 45 min. The improvement of pupils’ physical health was observed in the process of activities. It was revealed, that under the influence of health-improving running activities there took places the harmonious physical development, the economy of cardio-vascular system of organism increased, pulse at rest decreased. The mood, cheerfulness and mental working capacity increased. The training in school section is a beginning of active life, good mood, health, study. The section of health-improving walking and running gives a possibility to compensate the motor activity in the structure of school children’s motor regime, help to avoid hypodynamia and diseases